Developmental programmes in the evolution of Equisetum reproductive morphology: a hierarchical modularity hypothesis - Tomescu, Alexandru M F (2017)
Background: The origin of the Equisetum strobilus has long been debated and the fossil record has played an important role in these discussions. The paradigm underlying these debates has been the perspective of the shoot as node-internode alternation, with sporangiophores attached at nodes. However, fossils historically excluded from these discussions (e.g. Cruciaetheca and Peltotheca ) exhibit reproductive morphologies that suggest attachment of sporangiophores along internodes, challenging traditional views. This has rekindled discussions around the evolution of the Equisetum strobilus, but lack of mechanistic explanations has led discussions to a stalemate.